Implementation of Smart City Solution - Zaru, Daniil (2019)
This thesis deals with an implementation of a concept called Smart City, which is built on top of the IoT concept. Also, both of the concepts mentioned above are defined in this work including their development over the years and already existing solutions. Besides that, this paper discusses benefits and risks related to these concepts.The main goal of this work is to apply gathered theoretical knowledge on a real example. To do so, a part of the capital of the Czech Republic, Prague 2 is chosen. Status quo of Smart City in Prague is described in the thesis as well as the analysis of efficient opportunities for Smart City solution implementation. Furthermore, the impact on economical, technological, informational and social aspects of the city is covered.